Granny Gert and the Bunion Brothers - Enderle, Dotti 1954-; Kulka, Joe (Gretna : Pelican Pub., 2006)
When "the dumbest boys in Texas" both fall in love with the granddaughter of their new employer, they shirk their duties to fight over the beautiful Starla until Granny Gert threatens to sic Mad Dog on them.
Keywords: Brothers -- Fiction; Love -- Fiction; Tall tales; Texas -- Fiction